Evolutionary and Virulence Signatures of S. Maltophilia and S. Paucimobilis Uncovered Through Genomic and Proteomic Profiling - Abidfalhy, Majida Mohammad; Azeez, Zahraa Falah (American Journal of Biology and Natural Sciences, 2026)
This paper is a comparative study of Stenotrophomonas maltophilia and Sphingomonas paucimobilis using phenotypic, biochemical, genomic and proteomic characterization. There were 32 isolates that were obtained in the clinical and environmental sources (18 S. maltophilia, 14 S. paucimobilis). The growth (2436 h) and biofilm formation (83.3%, OD595: 0.28116) of S. maltophilia were higher and the maximum environmental tolerance was high (survivance in 8178.NaCl). Antibiotic susceptibility profiles indicated that S. maltophilia was largely multidrug resistant, with a resistance rate of 88.9-100 per cent. to β-lactam, up to 94.4 per cent. to carbapenem and 83.3 per cent. to aminoglycoses whilst S. paucimobilis only exhibited moderate resistance to β-lactam (4271) and high susceptibility to fluoroquinolones and tetracyclines. These results were supported by genomic analysis in which percentages of resistance and virulence determinants were found to be high in S. maltophilia at; smeDEF (100%), rmlA-D (94.4%), rpfF (88.9%), and fliC (83.3%), in comparison with the percentages at 73.5-35% in S. paucimobilis. The addition of MALDI-TOF MS greatly improved accuracy of identifications that produced 100 percent concordance with 16S rRNA sequencing and correct two mis-identifications created by VITEK 2. All these findings highlight the strong pathogenic potential and evolutionary specialization of S. maltophilia, and place S. paucimobilis as a low-virulence, but environment-adapted species.